Pharmaceutical modulation of the proteolytic profile of Transforming Growth Factor Beta induced protein (TGFBIp) offers a new avenue for treatment of TGFBI-corneal dystrophy - Venkatraman, Anandalakshmi (2021)
Corneal dystrophies are a group of genetically inherited disorders with mutations in the TGFBI gene affecting the Bowman's membrane and the corneal stroma. The mutant TGFBIp is highly aggregation-prone and is deposited in the cornea. Depending on the type of mutation the protein deposits may vary (amyloid, amorphous powdery aggregate or a mixed form of both), making the cornea opaque and thereby decreases visual acuity. The aggregation of the mutant protein is found to be specific with a unique aggregation mechanism distinct to the cornea. The proteolytic processing of the mutant protein is reported to be different compared to the WT protein. The proteolytic processing of mutant protein gives rise to highly amyloidogenic peptide fragments. The current treatment option, available for patients, is tissue replacement surgery that is associated with high recurrence rates. The clinical need for a simple treatment option for corneal dystrophy patients has become highly essential either to prevent the protein aggregation or to dissolve the preformed aggregates. Here, we report the screening of 2500 compounds from the Maybridge RO3 fragment library using weak affinity chromatography (WAC). The primary hits from WAC were validated by 15N-HSQC NMR assays and specific regions of binding were identified. The recombinant mutant proteins (4th FAS-1 domain of R555W and H572R) were subjected to limited proteolysis by trypsin together with the lead compounds identified by NMR assays. The lead compounds (MO07617, RJF00203 and, BTB05094) were effective to delay/prevent the generation of amyloidogenic peptides in the R555W mutant and compounds (RJF00203 and BTB05094) were effective to delay/prevent the generation of amyloidogenic peptides in the H572R mutant. Thus the lead compounds reported here upon further validation and/or modification might be proposed as a potential treatment option to prevent/delay aggregation by inhibiting the formation of amyloidogenic peptides in TGFBI-corneal dystrophy.